2004
DOI: 10.1093/mutage/geh041
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome fragility in two sheep flocks exposed to dioxins during pasturage

Abstract: In the last 3 years several farms raising cattle, river buffalo and sheep have been unable to sell dairy milk due to the presence of high levels of dioxins. Furthermore, several cases of abortion (around 25% of total births) and abnormal foetuses (2.5% of total births) were recorded in two flocks of sheep raised in the province of Naples where a higher level of dioxins (5.27 pg/g fat, as human WHO TCDD equivalent) have been found in the milk mass than that permitted (3.0 pg/g fat, as human WHO TCDD equivalent)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 15 publications
1
33
0
1
Order By: Relevance
“…In particular, dioxin pollution has occurred in Italy, especially in Campania and in industrial areas of Piedmont, Lombardy, Tuscany and Puglia (Biasioli and Ajmone-Marsan, 2007;Ingelido et al, 2009;Turrio-Baldassarri et al, 2009), leading to contamination of dairy milk in sheep, cattle and river buffaloes (Iannuzzi et al, 2004;Perucatti et al, 2006;Cirillo et al, 2008;Esposito et al, 2009). Dioxins are polyhalogenated aromatic hydrocarbons, highly toxic and persistent, present at low level in air, soil, water, feed as well as in foods such as dairy products (Matsumura, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, dioxin pollution has occurred in Italy, especially in Campania and in industrial areas of Piedmont, Lombardy, Tuscany and Puglia (Biasioli and Ajmone-Marsan, 2007;Ingelido et al, 2009;Turrio-Baldassarri et al, 2009), leading to contamination of dairy milk in sheep, cattle and river buffaloes (Iannuzzi et al, 2004;Perucatti et al, 2006;Cirillo et al, 2008;Esposito et al, 2009). Dioxins are polyhalogenated aromatic hydrocarbons, highly toxic and persistent, present at low level in air, soil, water, feed as well as in foods such as dairy products (Matsumura, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal aberrations were observed in Murrah buffaloes maintained in the vicinity of a pesticide factory by Sikka et al (1988). Similarly, chromosomal aberrations were reported in sheep flocks exposed to higher level of dioxins during pasturage (Iannuzzi et al 2004). However Murali et al (2007) observed no structural or numerical chromosomal anomalies in Friesian crossbred cattle inhabiting areas of raw leather processing industries.…”
Section: Chromosome Aberrationsmentioning
confidence: 74%
“…Additional high-resolution analyses of aphidicolin-induced breaks in cattle chromosomes will likely be required. One intriguing concept suggested by Nicodemo et al [2008], Iannuzzi et al [2004] and others is the idea that with standardization of chromosomal breakage, and fragile site locations, livestock in pastures could function as bio-markers of environmental contaminants. For implementation of this type of approach, sufficient statistical analyses will be required to establish the base frequency of fragile site expression in comparable unexposed populations.…”
Section: Bovidaementioning
confidence: 99%
“…This site was located at the distal end of the p arm and may correspond to FRAXB observed in other species. Gaps and breaks have been described in sheep ( Ovis aries ) exposed to dioxin [Iannuzzi et al, 2004]. Other reports include a rare fragile site was found on chromosome 8 in Romanov sheep [Matejka et al, 1990], fragile sites in Merino sheep [Cribiu et al, 1991], Aragonese rams [Pascual and Arruga, 1996], and British Suffolk sheep [Ali et al, 2008].…”
Section: Other Livestockmentioning
confidence: 99%